Project Engineering Primer for Chemical Engineers - Chakrabarti, Sampa; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book discusses financial, managerial and engineering aspects associated with project engineering. The book is a text/reference book on courses related to project engineering for undergraduate students of Chemical Engineering programmes. The author has utilized her decade-long professional experience with reputed project consultancy organizations and her academic experience in writing this book. The background of project engineering is described with special emphasis on its interdisciplinary nature. Project management techniques are discussed with the help of worked-out examples. It includes multiple choice questions and information regarding relevant courses in different institutes. The book is useful for undergraduate degree and diploma students as well as for fresh graduate engineering trainees in various process consulting organizations.
Introduction -- Pre-Project Work -- Basic Engineering -- Detailed Engineering -- Financial Aspects of Project Engineering -- Management Aspects of Project Engineering.
Keywords: Chemical engineering; Production engineering; Chemical Process Engineering; Chemical Engineering; Process Engineering; Chemical engineering -- Management; Project management